Acts of State and power disputes in the implementation of the State Policy for the Sustainable Development of Traditional Peoples and Communities in Minas Gerais: Constructions, challenges and limitations: Acts of State and power disputes in the implementation of the State Policy for the Sustainable Development of Traditional Peoples and Communities in Minas Gerais: Constructions, challenges and limitations - Costa Ribeiro, Gabriel (Revista Desenvolvimento Social, 2023)
The objective of this article is to establish, from the analytical-methodological perspective of studies on State and power relations, a genealogy of the State Commission of Traditional Peoples and Communities of Minas Gerais (CEPCT-MG), a consultative and deliberative political body responsible for monitoring and supervising the implementation of the State Policy for the Sustainable Development of Traditional Peoples and Communities of Minas Gerais (State Law No. 21,147/2014). The methodological procedures consist of empirical analysis, documentary research and application of theoretical framework inscribed in the field of Social Sciences. The case study presented provides valuable elements for understanding how the conduct of the Commission's work is the result of intense disputes over the monopoly of symbolic power, as well as the structures that enable the control exercised by State agents in the implementation of public policies for ethnic recognition, in the face of the prism of territorial guarantees and rights of traditional peoples and communities in Minas Gerais.